Challenging a dogma of exercise physiology: Does an incremental exercise test for valid V-dotO2max determination really need to last between 8 and 12 minutes? - Midgley, A. W.; Bentley, D. J.; Luttikholt, H.; McNaughton, L. R.; Millet, G. P. (Sports Medicine, 2008)
A widely cited recommendation is that to elicit valid maximal oxygen uptake (V-dotO2max) values, incremental exercise tests should last between 8 and 12 minutes. However, this recommendation originated from the findings of a single experimental study conducted by Buchfuhrer et al. in 1983. Although this study is an important contribution to scientific knowledge, it should not be viewed as sufficient evidence to support the recommendation for eliciting valid V-dotO2max values.